Quantification of sensory specific satiety and desire to eat bitter or sweet-bitter infusions of yerba mate in women with normal weight - García, Verónica (2023)
Among the beneficial properties of yerba mate, it has been proven that it produces a decrease in appetite, weight loss and a decrease in fat deposits. Sensory properties influence the palatability of food and ultimately influence the amount consumed. It isvery frequent that infusions of mate alone or sweetened produce judgments of the type "I drink mate and I am satiated". The aim of this study was to quantify the specific sensory satiety (SSS) and the desire to eat (DE) of these infusions in females with normal body weight.Thirty female university students and professors participated, who reported their weight and height to determine the body mass index (BMI). To determine the SSS and DE, 1.2% W/V (MT) mate infusion was prepared, 5% W/V sweetened MT with sugar (MT-A) or Stevia rebaudiana B extract at 0.03% P /V (MT-B). In all cases, the infusions were prepared by placing the mate bag containing 3 g of sample in contact with 250 ml of water at 90 °C for 6 minutes. The infusions were consumed at 70°C. For theSSS and DE evaluations, crackers, vanilla-flavored light yogurt, and unsweetened corn flakes were presented as controls. The consumers evaluated in three sessions the perceived pleasure/desire to eat before and after consuming a 250 ml cup of each infusion and a 4 g portion of the controls using unstructured scales of 100 mm length. The SSS and the DE were calculated as the difference of the magnitudes of pleasure pre and post ingestion introducing the correction factor calculated from the respective magnitudes assigned to the controls. Data were analyzed using the General Linear Model and Tukey´s test for post hoc contrasts to check for significant effects of reported SSS or DE for the three Infusions. Referring to the BMI, all the women reported weights and heights that denote normal weight (average BMI = 20.9). The appearance of satiety occurs both in MT, MT-A and MT-B (average SSE = -11.8) and there is also a decrease in the desire to eat after mate overload (average DE = -13.5). It can be concluded thatthe SSS and the DE, which regulate the cessation of intake, are maintained even though the caloric density and the taste of these infusions change. It remains to find out if these mechanisms are down regulated due to the increase in body weight, which would cause a lack of satiety and the desire to eat this type of infusions.